Protective effect of Amazonian Himatanthus sucuuba extracts in Drosophila melanogaster exposed to Paraquat (Research, Society and Development, 2022)
The Amazon rainforest is an essential source of scientific knowledge, so several research groups seek to understand the role of Amazonian compounds in diseases. Among the vast flora, Himatanthus sucuuba has a variety of therapeutic purposes and is used for the first time in the neuroprotection induced by Paraquat (PQ) in Drosophila melanogaster. In our study, we carried out phytochemical assays with the hydroalcoholic extract of H. sucuuba, revealing qualitatively classes of secondary metabolites and quantitatively total phenols (43.33 mg GAE/g extract-1), total flavonoids (44.09 mg GAE/G Extract- 1) and antioxidant activity via DPPH and ABTS. Furthermore, exposure of adult D. melanogaster (wild strain, Canton Special) to PQ for 15 days caused increased oxidative stress, as evidenced by elevated levels of protein carbonyls, lactate, and acetylcholinesterase and citrate synthase activities. However, the diet supplemented with H. sucuuba (0.1 mg/mL) for 15 days prevented damage from oxidative stress triggered by PQ. Our study aims to demonstrate the protective effect of H. sucuuba extract on D. melanogaster exposed to PQ. Based on our results, we suggest that extracts from the bark of H. sucuuba can prevent or minimize human diseases caused by oxidative stress. Therefore, further studies on the mechanisms involved in such activities will be necessary.